2021
DOI: 10.1007/s10570-020-03675-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical characterisation of a water-repelling terpolymer coating of cellulosic fibres

Abstract: Polymer coatings on cellulosic fibres are widely used to enhance the natural fibre properties by improving, for example, the hydrophobicity and wet strength. Here, we investigate the effects of a terpolymer P(S-co-MABP-co-PyMA) coating on cotton linters and eucalyptus fibres to improve the resistance of cellulose fibres against wetness. Coated and uncoated fibres were characterised by using scanning electron microscopy, contact angle measurements, Raman spectroscopy and atomic force microscopy with the objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The Derjaguin-Muller-Toporov (DMT) model implemented in the Nanosope Analysis (V2.0) software was used to obtain the modulus and adhesion force mapping during the PFQNM measurements, where the localized Young´s module (denoted as modulus or DMT modulus in the following texts) and adhesive force at any interesting location of a PFQNM image were calculated. The DMT model includes adhesion outside the contact area and is suitable for high elastic moduli, low adhesion and a small radius of indentation and was proven to be suitable for nanocellulose studies [ 19 , 38 ]. In our case, it is a safe approximation because indentations are small, adhesion is weak in aqueous environments, and there is an acceptable difference of ca.…”
Section: Methodsmentioning
confidence: 99%
“…The Derjaguin-Muller-Toporov (DMT) model implemented in the Nanosope Analysis (V2.0) software was used to obtain the modulus and adhesion force mapping during the PFQNM measurements, where the localized Young´s module (denoted as modulus or DMT modulus in the following texts) and adhesive force at any interesting location of a PFQNM image were calculated. The DMT model includes adhesion outside the contact area and is suitable for high elastic moduli, low adhesion and a small radius of indentation and was proven to be suitable for nanocellulose studies [ 19 , 38 ]. In our case, it is a safe approximation because indentations are small, adhesion is weak in aqueous environments, and there is an acceptable difference of ca.…”
Section: Methodsmentioning
confidence: 99%
“…fiber coating, improving hydrophobicity and wet strength. [AUERNHAMMER et al, 2021] A further challenge concerning paper material's mechanical properties for construction occurs regarding its time dependent behavior. Investigations on the creep behavior show that additional deformations as well as retarded failure of paper is to be expected when put under structural loads.…”
Section: General Propertiesmentioning
confidence: 99%
“…However, (Mantanis et al 1995) recorded the swelling of cellulose single fibres in water and showed that equilibrium was reached at 45 minutes. We performed the measurements in the wet state according to (Auernhammer et al 2021). Additionally, the water drop for swelling was removed before the measurement, preventing the fibre from swelling further.…”
Section: Fibresmentioning
confidence: 99%